Impact of SME-suitable Business Area Designation on the Korean Tofu Market - Jinkook Lee (Korea Development Institute (KDI), 2015)
The SME-suitable industry designation scheme aims to foster the growth of Korea's SMEs by restricting the entry or expansion of large enterprises. However, without a full understanding of specific business areas, the restrictive measures can undermine SMEs' profit as well as consumer welfare. The scheme should be intricately implemented based on both prior investigation and ex-post analysis at product level. In the case that the prior investigation reveals little substitutability between SME-made and large enterprise-made products, it would be more prudent to not designate the business as SME-suitable. Additionally, business areas that are found to have suffered from a shrinking market and falling profits (SMES) via ex-post analysis should not be subject for renewal or extension. - More than three years have passed since the designation scheme was initiated, but disputes over its efficacy are still ongoing. - This study analyzes the economic effect of the designation scheme with the focus on the Korean tofu market, which is currently under intense debate over its suitability as a SME business area. - Once designated as 'SME-suitable,' the business area is not accessible to large enterprises and their expansion is restricted for the initial three years. - The point of the recent disputes was on the redesignation of soon-to-be expired industries. There were heated arguments about the pros and cons among large, medium- and small-sized companies. - Analysis of the economic effects of the scheme must be conducted separately for each industry, reflecting the features of the companies and characteristics their products. - The tofu manufacturing business has grown consistently until recently, but posted slowing growth in 2012 and negative growth in 2013. - The declining rate of growth in the tofu market is caused by the slowing growth rate of the packed tofu market, due to the decreased sales of large enterprises affected by the designation scheme. - Responding to the designation scheme, large enterprises reduced the production of domestic soybean tofu and expanded that of imported soybean tofu. - Compared to imported soybean-based products, domestic soybean-based products are sold at a higher price and reap in smaller total profits, meaning that limiting sales will inevitably weaken the incentive to produce. - As large enterprises expanded their production of imported soybean-based products, the market witnessed heightened competition and stagnated sales of SMEs. - Since the scheme was adopted, consumer welfare has suffered a loss of approximately 2.4 billion won (5.5%) on a monthly average basis, or 28.7 billion won on an annual basis. - Large enterprises are estimated to have experienced a loss of 19.5% in profit in 2014, compared to 2011. The drop is particularly steep in domestic soybean products. - The designation scheme needs to be managed in a highly selectively, considering the characteristics of each industry. - Ironically, the scheme developed with an intent to encourage the growth of SMEs has undermined the profitability of not only large enterprises but also SMEs. - The designation scheme should be implemented with more finesse based on thorough prior market investigation and ex-post analysis at the product level and on product characterisitcs.
Keywords: 330